The role of monetary and fiscal policies in handling the global financial crisis : effects and defects. - Lum, Wan Teng. (2010)
The boom of the world economy during 1990-2007 made economists envisage that recessions are a phenomenon of the past, and through careful study and understanding of world economies, setbacks in the business cycle can be combated (Krugman, P., 2009). However the Global Financial Crisis (GFC) showed that a capitalist economy cannot survive if it oscillates between the threats of an imminent collapse of asset values and employment, and threats of inflation and rampant speculation, especially if these threats become realized (Minsky, 1989).